Customer Service and Delivery Service Quality of Delivery Service Companies - Rachmi, Irsafanti; Setiawan, Edhie Budi; Pahala, Yosi; Veronica, Veronica; Setiawan, Ferdy Trisanto (Institut Transportasi dan Logistik Trisakti, 2024)
The development of goods delivery services could be seen from the growth of service companies’ quantity domestically and abroad. People could determine which delivery services they will use based on their will and the service quality. Freight forwarding companies often experience difficulty in retaining delivery services’ loyal customers. The purpose of the study is to analyze the influence of satisfaction, service quality, and customer’s services on customer’s loyalty of the freight forwarder company. The research technique used the Quantitative approach that the survey data was collected and processed using Structural Equation Modeling (SEM) method of AMOS 22 software. This research used 200 purposive sampling of the company’s customers as respondents. The results show that there is direct and indirect influence of customer’s satisfaction, service quality, and customer’s service on customer’s loyalty. Therefore, the role of service quality and customer’s satisfaction has a significant impact on the business continuity of freight forwarding service companies. It means that the freight forwarding company should maintain the customer’s loyalty optimally by increasing customer’s satisfaction through the quality of service provided to customers in order to build the customer’s loyalty.